PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA PADA TINDAK PIDANA EKSPLOITASI TERHADAP ANAK - Laia, Fariaman; Laia, Laka Dodo; Ndruru, Antonius (LPPM Universitas Nias Raya, 2024)
In cases of criminal acts of exploitation of children, many still occur in the territory of the Unitary State of the Republic of Indonesia, and this is very likely to occur because there are several ways to destroy the economy of each person and also fulfill the interests of individuals who take advantage of this opportunity so that in this situation it occurs. this exploitation. The type of research used in this research is normative legal research. In resolving the legal problems that occurred in this research, the author also used the statutory approach, case approach and analytical approach methods. The author uses secondary data collection to draw conclusions from general to specific. So from these results the author believes that, in the judge's consideration of child exploitation carried out by certain elements the judge must reflect the applicable law even though the judge is not only a mouthpiece for the applicable law but at least the judge can look further into the future of the child himself. . The conditions experienced, mental and physical. It must really be able to be recovered well. The judge must be able to provide a deterrent effect on the perpetrator to break the chain of crimes, as in the discussion the term punishment theory is known as a theory of retaliation in correcting crimes against children themselves. The state must also be present in protecting its citizens, as well as parents in the current situation must be really wary because there are so many methods used by each person so that their interests can be achieved.